EFFECT OF TEMPERATURE AND CASSAVA GENOTYPE ON THE DEVELOPMENT, FECUNDITY AND REPRODUCTION OF Bemisia tabaci SSA1 - KATONO, K.; MACFADYEN, S; OMONGO, C.A; COLVIN, J.; KARUNGI, J.; OTIM, M.H (African Crop Science Journal, Vol. 30, No. 2, pp. 185 - 203, 2022)
The Bemisia tabaci complex is currently recognised as key agricultural pests that cause economic damage globally. Temperature is the most important driver of changes in behaviour, abundance and distribution of insect pests, including the whitefly (Bemisia tabaci). The objective of this study was to evaluate the development, fecundity and reproduction of B. tabaci SSA1 on cassava genotypes under a range of temperatures. A laboratory study was conducted using three cassava genotypes (Alado alado, NAROCASS 1 and NASE 14) at five constant temperatures (16, 20, 24, 28 and 32 °C). The parameters assessed included development duration, survival, fecundity and population parameters for B. tabaci SSA1. Temperature had significant effects (P<0.001) on development time, survival and fecundity of B. tabaci; while cassava genotype had no effect (P>0.05). An inverse relationship was observed between development time and temperature for all stages across all cassava genotypes. The total life cycle was 63.8 days at 16 °C and 17.9 days at 32 °C on NAROCASS 1. Survival for each stage throughout the entire life cycle increased with temperature and was highest at 32 °C, although this was not significantly different from that at 28 °C. Fecundity increased with temperature and was highest at 32 °C on all cassava genotypes. For all cassava genotypes, the intrinsic rate of increase (rm ), finite rate of increase (λ) and net reproductive rate (Ro ) increased with temperature, while mean generation time (T) reduced following a similar pattern. At 32 °C, rm , Ro , λ and T were 0.2, 48.7, 1.2 and 22.6 days, respectively; compared to 0.01, 1.9, 1.0 and 71.2 days at 16 °C on Alado alado. Therefore, the ideal development temperature for B. tabaci SSA1 is 32 °C. Thus, there is a risk of accelerated future expansion of B. tabaci SSA1 populations globally, with global warming and climate variability.
Keywords: Climate Change; net reproductive rate